Answer: y = 3x + 6
Explanation:
The equation of a straight line can be represented in the slope intercept form as
y = mx + c
Where
m = slope = (change in the value of y in the y axis) / (change in the value of x in the x axis)
The equation of the given line is
y = 3x - 4
Comparing with the slope intercept form, slope = 3
If two lines are parallel, it means that they have the same slope. Therefore, the slope of the line passing through (-2, 0) is 3
To determine the intercept, we would substitute m = 3, x = - 2 and y = 0 into y = mx + c. It becomes
0 = 3 × - 2 + c = - 6 + c
c = 0 + 6 = 6
The equation becomes
y = 3x + 6